Functional outcomes of ischemic stroke patients aged over 80 years treated with acute revascularization therapy according to pre-morbid disability: a PARADISE study - Ruel, Ségolène; Baptiste, Laura; Duloquin, Gauthier; Béjot, Yannick (Frontiers in Neurology, 2023)
Introduction – Aging population leads to changes in the profile of patients with acute ischemic stroke (IS), and older adults were largely excluded from randomized clinical trials of acute revascularization therapy. This study aimed to assess functional outcome of treated IS patients >80 years old according to prior disability, and identify associated factors. Methods – Consecutive older patients with acute IS treated with either IV thrombolysis and/or mechanical thrombectomy were enrolled between 2016 and 2019. Premorbid handicap was assessed using the modified Rankin Scale (mRS) score and patients were classified as being independent (mRS score 0-2), or having pre-existing handicap (mRS score 3-5). Multivarable logistic regression analysis was performed to assess factors associated with a poor functional outcome (mRS score >3) at 3 and 12 months, in each group of patients. Results – Among 300 included patients (mean age: 86.3 ± 4.6 years, 63% women, median NIHSS score: 14, IQR: 8-19), 100 had pre-existing handicap. In patients with premorbid mRS 0-2, 51% had mRS >3 including 33% of deaths at 3 months. At 12 months, 50% had a poor outcome including 39% of deaths. In patients with premorbid mRS 3-5, 71% had a poor outcome at 3 months including 43% of deaths and at 12 months, 76% had mRS >3 including 52% died patients. In multivariable models, NIHSS score at 24 hours was independently associated with poor outcome at 3 months and 12 months in both patients with (OR=1.32; 95% CI: 1.16-1.51, p<0.001 for 12 months outcome) or without (OR=1.31; 95% CI: 1.19-1.44, p<0.001 for 12 months outcome) premorbid handicap. Conclusion - Although a large proportion of older patients with pre-existing handicap had a poor functional outcome, they did not differ from their not-impaired counterparts regarding prognostic factors. This means that there were no factors in our study that would help clinicians identify patients at risk of poor functional outcome after revascularization therapy among those with prior disability. Further studies are needed to better understand the post-stroke trajectory of older IS patients with premorbid handicap.